Repeated Single Candidate Local Elections in Indonesia: Political Party Pragmatism in North Bengkulu and Ngawi - Syahid, Imam; Asbudi; Mujiburrahman; Rafdi, Hashfi; Pratama, M. Aviv Adhitya Putra (Kemudi, 2026)
The recurrence of single candidate regional head elections in North Bengkulu and Ngawi Regencies in the 2020 and 2024 elections raises questions about the effectiveness of institutional reform in expanding local electoral competition. Although Constitutional Court Decision Number 60/PUU-XXII/2024 lowered the nomination threshold and theoretically opened wider opportunities for political parties to nominate alternative candidates, this study shows that such institutional change did not automatically alter the configuration of electoral contests in the two regions. This study uses a qualitative method with a descriptive approach, utilizing secondary data from official election documents, Constitutional Court decisions, laws and regulations, academic publications, and media reports related to regional head elections in North Bengkulu and Ngawi Regencies. The analysis employs the perspective of political party pragmatism and the office-seeking orientation in coalition formation. The results of the study show that the recurrence of single-candidate elections was shaped by the consolidation of political party support into large coalitions behind dominant candidates who possessed strong political capital, incumbency advantages, wider political networks, and higher electability. Under these conditions, political parties, including smaller parties, tended to prioritize electoral victory and access to power rather than promote alternative candidates. As a result, coalition building became increasingly pragmatic and contributed to the weakening of electoral competition across two consecutive electoral periods. This study shows that the recurrence of single-candidate elections is better understood not merely as an institutional issue, but as a reflection of pragmatic political party behavior in local electoral politics.